Estimation of Biomass and Carbon Stocks in Mangrove Forests Dominated by Nypa fruticans Wurmb in the Nagari Mandeh Area, West Sumatra, Indonesia - Nur Aisyah Fikri; Solfiyeni; Tesri Maideliza; Muhammad Azli Ritonga (Department of Forestry, Faculty of Agriculture, University of Lampung, 2026)
Ecosystem condition, biomass, and carbon storage in mangrove forests are highly dependent on the presence of mangrove species in coastal ecosystems. Conversely, the presence of a dominant species alters ecosystem mechanisms; for example, Nypa fruticans Wurmb. Biomass, carbon storage, and potential carbon sequestration were estimated in a coastal area dominated by N. fruticans. Sampling was conducted by laying out multi-level plots along transect lines representing different vegetation types. Biomass on the ground surface was calculated by applying species-specific allometric equations to convert biomass to carbon and CO2 equivalents, and then computing the total carbon stocks. Biomass was calculated at 140.21 tons/ha, with a carbon stock of 66.11 tons/ha, yielding a carbon sequestration potential of 241.82 tons/ha. It is obvious that N. fruticans, the dominant species as the biggest carbon store, is accompanied by low diversity of native mangrove species. Ecological imbalance between N. fruticans and other species persists despite increased total carbon storage. Management efforts must be implemented to support biodiversity and carbon sequestration in coastal mangrove forests. Keywords: biomass, carbon stock, mangrove, Nypa fruticans, carbon sequestration